Multi-channel management: an exploratory study of current practices. (1st January 2013) - Wakolbinger, Lea M.; Stummer, Christian
While web services have enabled seamless interoperability among heterogeneous IT implementations for multiple channels, innovative information and business services may further advance multi-channel integration. In investigating current practices of multi-channel management as a prerequisite for developing proper services, this paper may prepare the ground for such endeavours. It provides a literature review as well as insights from interviews with practitioners from top and middle management in major firms operating multiple channels in Austria. We discuss competitive advantages as well as challenges to be faced when establishing multiple distribution channels, e.g., by adding a mobile channel to an existing brick-and-mortar store, and outline measures of coordinating and integrating multiple channels. It can be shown, that multi-channel practice considerably differs between industries. Multi-channel integration activities, in particular, so far only play a minor role, but constitute a promising field of research in the forthcoming decade.